Rozwijanie autonomii ucznia w pracy z uczniem niezwykłym - Pawlak, Mirosław (Neofilolog, 2019)
Fostering learner autonomy is undoubtedly one of the most important goals of foreign language education in Poland, which is evidenced by the fact that it has been included in the current national curriculum, it figures prominently in virtually all available syllabi, and modern coursebooks in-clude numerous elements intended to assist its implementation. It should be made clear, however, that the development of an autonomous approach to language learning is by no means an easy task, the success of which is to a large extent dependent on a particular student. Thus, the aim of the present paper is to demonstrate how autonomy can be effectively pro-moted in the case of exceptional learners, both such who are successful and such for whom learning a foreign language poses a formidable challenge.